Spain, China and Japan in Manila, 1571-1644 local comparisons and global connections - Tremml, Birgit (Emerging Asia, 2015)
"This book examines the connected histories of Spain, China and Japan as they emerged and developed following the foundation of Manila as capital of the Spanish Philippines in 1571. Cross-cultural encounters not only shaped Manila's development as a "Eurasian" port city, but also had profound political, economic, and social ramifications for the three pre-modern states involved. This becomes obvious when looking into the diverse nature of long-distance trade, including trans-Pacific silver-for-silks bargaining, direct Sino-Japanese exchange, and provisions trade. In order not to overlook the role of human beings involved in proto-global struggles for power and foreign trade control, this volume combines a systematic comparison with a focus on different actors and their agency. The author offers an example of empirical global history based on multilingual primary source research and a critical evaluation of different historiographical traditions. Integrating Manila into world history helps in revising many long held misconceptions by replacing them with a more balanced, multi-faceted view"--Back cover.